2442. Outcomes in ESBL Bacteremia Empirically Treated With Piperacillin/Tazobactam or Carbapenems. (26th November 2018) - John, Reeba; Colley, Peter; Nguyen, Hoa; Berhe, Mezgebe
Abstract: Background: Infections due to extended spectrum β-lactamase (ESBL) producing bacteria are problematic due to the association with worse outcomes and limited treatment options. Carbapenems (CBPs) remain the drugs of choice for these infections due to evidence of a mortality benefit and the mixed clinical efficacy associated with piperacillin/tazobactam (PTZ) despite often reported in vitro activity. While definitive treatment for these infections has been well-defined, evidence for appropriate empiric therapy remains inconclusive. Rapid molecular assays capable of identifying ESBL markers may aid in switching to appropriate definitive therapy sooner and spare empiric carbapenem use. Methods: This multicenter retrospective study at 9 sites at Baylor Scott & White Health included patients with a positive blood culture with ESBL-producing bacteria identified by rapid molecular assay from January 1, 2014 to September 22, 2017 and were empirically prescribed either PTZ or a CBP. Patients were excluded if they continued PTZ for more than 24H after identification or did not receive a CBP for definitive therapy. Categorical data were analyzed using the Fisher's exact test and continuous data were evaluated using the t-test and Wilcoxon rank-sum test. Results: 117 patients met inclusion criteria of which 66 and 51 received empiric PTZ or CBPs, respectively. Baseline characteristics were similar between the groups, including suspected source of bacteremia, prior hospital stay, prior antibiotic therapy, history of positive non-blood ESBL culture, ICU admission, and time to ESBL identification. There was no difference in hospital mortality (3 vs. 7.8%, P = 0.4), hospital length of stay (6.1 vs. 5.9%, P = 0.88), ICU length of stay (4.7 vs. 3.3%, P = 0.39) or recurrent ESBL bacteremia (7.6 vs. 7.8%, P = 0.99) between those that received PTZ or a CBP for initial treatment, respectively. Conclusion: This study in patients with ESBL bacteremia showed similar outcomes when treated empirically with PTZ or a CBP. In the era of rapid molecular assays, these results suggest that empiric PTZ use and avoidance of empiric CBP therapy in the first 24H of infection can be considered until a microbiological diagnosis is confirmed. Disclosures: All authors: No reported disclosures.